High-quality III-V compound substrates and their preparation methods
By coating a uniformly dispersed group III metal-organic source hybrid precursor with nanomaterials on a substrate, and combining MOCVD and HVPE technologies, the dislocation and stress problems in the preparation of high-quality GaN single crystal substrates were solved, and the growth of high-quality group III-V compound substrates was achieved.
Patent Information
- Application Number
- CN202111427468.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-26
- Publication Date
- 2025-10-31
- Estimated Expiration
- 2041-11-26
AI Technical Summary
Existing technologies make it difficult to prepare high-quality GaN single-crystal substrates, resulting in high dislocation density and stress in epitaxially grown crystal materials, which easily leads to warping cracks, affecting device efficiency and lifespan. Furthermore, growth on large-size substrates is even more challenging.
A group III metal-organic source hybrid precursor containing uniformly dispersed nanomaterials is coated onto a substrate, and a group III-V compound nanostructure is formed by MOCVD and HVPE technology to gradually release stress and grow a high-quality group III-V compound substrate.
It reduces dislocation density and residual stress, improves crystal quality, and enables the preparation of high-quality III-V compound substrates, suitable for substrates of different sizes.
Smart Images

Figure CN114121621B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a high-quality III-V compound substrate and its preparation method, belonging to the field of semiconductor material preparation technology. Background Technology
[0002] Recently, III-V compound semiconductor materials have been used extensively in optoelectronic devices, optoelectronic integration, ultra-high-speed microelectronic devices, and ultra-high-frequency microwave devices and circuits, showing great promise.
[0003] GaN materials can be used to fabricate high-frequency, high-power, and high-temperature resistant microelectronic devices, enabling optoelectronic devices with emission wavelengths covering the entire visible light band. They have enormous application prospects in aerospace and military fields, as well as in commercial fields such as everyday lighting and displays.
[0004] Currently, the more mature HVPE and MOCVD epitaxy techniques for preparing GaN materials are both epitaxial technologies grown on heterogeneous substrates. Due to the lattice and thermal expansion mismatch between the substrate and the epitaxial layer, the dislocation density and stress of the epitaxially grown crystal material are relatively high, which easily leads to warping cracks and other phenomena, affecting the working efficiency and lifespan of the device and restricting its application in the semiconductor electronics field. Homogeneous epitaxy on GaN single crystal substrates can greatly improve the crystal quality of the epitaxial film, reduce the dislocation density, and improve the working life and luminous efficiency of the device. Therefore, there is an urgent need for high-quality GaN single crystal materials to peel off the GaN substrate and realize homogeneous epitaxy technology.
[0005] However, the preparation of GaN bulk single crystal materials is very difficult. Due to the lack of matching substrates, the growth of GaN epitaxial materials is very difficult. In addition, with the development of markets such as semiconductor lighting and display, the demand for substrates is increasingly shifting to larger sizes, which poses greater difficulties and challenges to the growth of GaN materials.
[0006] Currently, GaN substrate materials are generally grown using separate MOCVD and HVPE epitaxy processes both domestically and internationally. This involves first growing a GaN template layer on a substrate such as sapphire using MOCVD, then growing a thick GaN film on the GaN template layer using HVPE, and finally peeling off the sapphire substrate. While significant progress has been made in producing high-quality GaN materials, compared to other semiconductor materials, thick GaN films grown on substrates such as sapphire still exhibit a high defect density. These dislocations act as non-radiative recombination centers during device operation, affecting device efficiency and causing increased leakage current, leading to rapid device aging. Furthermore, the residual stress in the GaN thick film on large-size heterogeneous substrates such as sapphire, resulting in warping cracks, is a difficult problem to overcome in GaN heteroepitaxial technology.
[0007] To grow high-quality GaN self-supporting substrates, various substrate processing techniques have been reported. By processing substrates such as sapphire, buffer layers for GaN material growth can be obtained, which can not only reduce dislocation density and residual stress, but also play an important role in the separation of GaN substrates. In addition to etching the substrate to give it different structures, Oshima et al. grew a TiN nanonetwork structure on a sapphire substrate as a buffer layer for HVPE growth of GaN substrates. The TiN nanonetwork also plays a significant role in the separation of GaN and sapphire substrates. There are also reports of using SiNx as a buffer layer to prepare GaN substrates. Similarly, there are reports of using two-dimensional sheet BN and graphene or carbon nanotubes coated on the substrate as intercalation layer structures to obtain self-supporting GaN substrates. However, the substrate processing techniques for these intercalation layer structures are relatively complex.
[0008] InAs substrates can be used to fabricate infrared light-emitting devices and quantum cascade lasers, and are widely used in gas detection, medical, and low-loss fiber optic communication. As a substrate material, GaAs substrates are used in integrated circuits and microwave devices, while InP substrates are widely used in millimeter-microwave electronic devices and optoelectronic devices for fiber optic communication. With the continuous improvement of device performance and the continuous maturation of device technology, the industrial production of single-crystal substrates with good lattice integrity, low dislocation density, suitable electrical parameters and high uniformity has placed higher requirements on them. Summary of the Invention
[0009] The main objective of this invention is to propose a high-quality III-V compound substrate and its preparation method based on the current technical challenges of heteroepitaxial materials, so as to overcome the shortcomings of the existing technology.
[0010] To achieve the aforementioned objectives, the technical solution adopted by this invention includes:
[0011] This invention provides a method for preparing a high-quality III-V compound substrate, comprising:
[0012] Provides a mixed precursor of group III metal-organic sources containing uniformly dispersed nanomaterials;
[0013] The group III metal-organic source mixed precursor is coated onto a substrate to obtain a group III metal-organic source mixed precursor coating layer. Then, the substrate with the group III metal-organic source mixed precursor coating layer is placed in an MOCVD reaction chamber, and a group III metal-organic source is introduced. Annealing and recrystallization are carried out in a mixed atmosphere of group V element source and reducing gas to form uniformly distributed nanomaterials and group III-V compound nanostructures. Group III-V compounds are further grown to obtain a group III-V compound template layer.
[0014] A thick film of III-V compound is grown on the template layer of the III-V compound to obtain a high-quality III-V compound substrate.
[0015] In some embodiments, the nanomaterials include any one or more combinations of zero-dimensional nanomaterials, one-dimensional nanomaterials, two-dimensional nanomaterials, and three-dimensional nanomaterials.
[0016] In some embodiments, the group III elements contained in the group III metal-organic source include any one or a combination of two or more of indium, gallium, and aluminum.
[0017] Furthermore, the group V element source contains any one or a combination of two or more of nitrogen, phosphorus, and arsenic.
[0018] This invention also provides high-quality III-V compound substrates prepared by the aforementioned method.
[0019] Compared with the prior art, the present invention has significant advantages and beneficial effects, specifically reflected in the following aspects:
[0020] 1) The present invention provides a high-quality III-V compound substrate and its preparation method. By spin-coating a metal-organic source hybrid precursor coating layer as a stress relief buffer layer, the dislocation density and residual stress of the nitride template layer can be reduced, thereby improving the crystal quality of subsequent III-V compound materials.
[0021] 2) In the MOCVD process of this invention, during the heating and introduction of group V element sources and reducing gas for annealing and recrystallization, the metal-organic source coating layer with dispersed nanomaterials gradually forms two types of crystal nuclei: nanomaterials and group III-V element compound nanostructures, and the stress of the epitaxial layer is gradually released.
[0022] 3) The nanomaterials and III-V group element compound nanostructures of the present invention can provide epitaxial growth nuclei, while strengthening the lateral epitaxial growth of the nitride template layer, inhibiting dislocation density extension, reducing the defect density of III-V group compound materials, and improving their growth quality.
[0023] 4) The present invention can control the thickness of the template layer grown by MOCVD process to match different thicknesses of HVPE grown III-V compound thick films, and prepare high-quality III-V compound substrates of different thicknesses on substrates of different sizes.
[0024] Other features and advantages of the invention will be set forth in the following description, and will be apparent in part from the description, or may be learned by practicing specific embodiments of the invention. The objects and other advantages of the invention may be realized and obtained by means of the structures particularly pointed out in the written description, claims, and drawings. Attached Figure Description
[0025] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0026] Figure 1 This is a schematic diagram of the fabrication process of a high-quality GaN substrate in a typical embodiment of the present invention. Detailed Implementation
[0027] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The components of the embodiments of the present invention described and shown in the accompanying drawings can be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments of the invention. Based on the embodiments of the present invention, those skilled in the art should understand that modifications can still be made to the technical solutions of each embodiment, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention. All other embodiments obtained without creative effort are within the scope of protection of the present invention.
[0028] It should be noted that similar reference numerals and letters in the following figures indicate similar items; therefore, once an item is defined in one figure, it does not need to be further defined and explained in subsequent figures. Furthermore, in the description of this invention, directional and ordinal terms are used only to distinguish descriptions and should not be construed as indicating or implying relative importance.
[0029] The following will provide a further explanation of the technical solution, its implementation process, and its principles.
[0030] One aspect of this invention provides a method for preparing a high-quality III-V compound substrate, comprising:
[0031] Provides a mixed precursor of group III metal-organic sources containing uniformly dispersed nanomaterials;
[0032] The group III metal-organic source mixed precursor is coated onto a substrate to obtain a group III metal-organic source mixed precursor coating layer. Then, the substrate with the group III metal-organic source mixed precursor coating layer is placed in an MOCVD reaction chamber, and a group III metal-organic source is introduced. Annealing and recrystallization are carried out in a mixed atmosphere of group V element source and reducing gas to form uniformly distributed nanomaterials and group III-V element compound nanostructures. Group III-V compounds are further grown to obtain a group III-V compound template layer.
[0033] A thick film of III-V compound is grown on the template layer of the III-V compound to obtain a high-quality III-V compound substrate.
[0034] In some embodiments, the nanomaterials include, but are not limited to, any one or more combinations of zero-dimensional nanomaterials, one-dimensional nanomaterials, two-dimensional nanomaterials, and three-dimensional nanomaterials.
[0035] Furthermore, the mass ratio of nanomaterials to group III metal-organic sources in the hybrid precursor is less than 1:1.
[0036] In some embodiments, the nanomaterial can be nanoparticles, preferably any one or a combination of two or more of metallic nanomaterials, non-metallic inorganic nanomaterials, and organic compound nanomaterials, and multiple nanoparticles coexist in the dispersion without reacting with each other, and still exist as individual nanoparticles in the dispersion.
[0037] Furthermore, the morphology of the nanomaterial can be any one or a combination of two or more of nanoparticles, nanowires, nanofilms, and nanobulks, but is not limited thereto.
[0038] In some embodiments, the nanomaterial (i.e., nanoparticles) may be any one or a combination of two or more of the following: Si3N4, SiO2, GaN, AlN, InN, SiC, ScAlN, Al2O3, Si, C, TiC, TiN, WC, WC-Co, B4C, BN, TiB2, LaF3, MoS2, ZrB2, ZnS, ZnSe, ZnO, Fe3O4, Ta2O5, SnO2, TiO2, ZrO2, Ni, Au, Ag, Fc, Co, Mn, Ti, Mg, Al, Ga, In, polystyrene, perovskite, graphene, etc., but is not limited thereto, and may also be any other possible nanoparticles.
[0039] Furthermore, the nanomaterials preferably include any one or a combination of two or more of the following: SiN, SiO2, GaN, AlN, InN, SiC, ScAlN, Al2O3, Si, C, TiC, TiN, BN, ZnS, ZnSe, ZnO, TiO2, Ni, Au, Ag, Fe, Co, Mn, Ti, Mg, Al, and graphene.
[0040] Furthermore, the nanomaterials preferably include any one or a combination of two or more of the following: SiN, GaN, AlN, SiC, ScAlN, Al2O3, TiO2, Ni, Al, Ga, and graphene.
[0041] Furthermore, the diameter of the nanomaterial is 5–500 nm.
[0042] In some embodiments, the group III elements contained in the group III metal-organic source include any one or a combination of two or more of indium (In), gallium (Ga), and aluminum (Al).
[0043] Furthermore, the group III metal-organic source includes a group III organic compound source, which includes any one or a combination of two or more of indium, gallium, and aluminum sources.
[0044] The indium (In) source includes one or more combinations of trimethylindium, triethylindium, and dimethylethylindium; the gallium (Ga) source includes one or more combinations of trimethylgallium (TMG), triethylgallium, and triisopropylgallium; and the aluminum source includes any one or more combinations of trimethylaluminum, triethylaluminum, dimethylalkanedaluminum, dimethylaluminum hydride, and aluminum alkyl complexes, but is not limited thereto.
[0045] In some embodiments, the group V element source contains any one or a combination of two or more of nitrogen (N), phosphorus (P), and arsenic (As).
[0046] Furthermore, the group V element source includes any one or a combination of two or more of nitrogen, phosphorus, and arsenic sources.
[0047] The nitrogen source includes any one or a combination of two or more of NH3, organic amine compounds, and trap compounds, but is not limited thereto. The organic amine compound may be an alkylamine, such as tert-butylamine or n-propylamine, and the trap compound may be a dimethyl trap, but is not limited thereto.
[0048] The phosphorus source includes PH3 and / or an organic phosphorus source, and the organic phosphorus source includes, but is not limited to, tert-butylphosphine.
[0049] The arsenic source includes AsH3 and / or an organic arsenic source, wherein the organic arsenic source includes, but is not limited to, tert-butylarsenic.
[0050] Furthermore, the reducing gas preferably includes H2, but is not limited thereto.
[0051] Furthermore, the flow rate ratio of the group V element source to the reducing gas in the mixed atmosphere is 10:1 to 100:1.
[0052] Furthermore, the thickness of the group III metal-organic source hybrid precursor coating layer is 20–2000 nm.
[0053] Furthermore, the substrate may be sapphire, silicon, silicon carbide, etc., but is not limited to these.
[0054] In some specific embodiments, the method for preparing the high-quality III-V compound substrate includes the following steps:
[0055] 1) The nanomaterials are uniformly mixed with a group III metal-organic source and ultrasonically treated at 5–40°C for 10–60 min to obtain a mixed precursor of a group III metal-organic source containing uniformly dispersed nanomaterials.
[0056] 2) In an N2 atmosphere, the mixed precursor is coated onto a substrate using a spin coating method to form a group III metal-organic source mixed precursor coating layer with a thickness of 20 nm to 2000 nm on the substrate.
[0057] 3) The substrate with a group III metal-organic source coating is placed in the reaction chamber of the MOCVD growth equipment. The pressure in the reaction chamber is 100-600 mbar. A group III metal-organic source, which is a group III organic compound source, is introduced. The reaction chamber is heated to 500-1200°C. A group V element source and a reducing gas are introduced for annealing and recrystallization for 10-100 seconds to grow a group III-V compound template layer with a thickness of 0.01-1 μm.
[0058] 4) A thick film layer of III-V compound with a thickness of 100-1000 μm is grown on the template layer of the III-V compound using the HVPE method;
[0059] 5) The substrate is peeled off to obtain a high-quality III-V compound substrate.
[0060] Furthermore, the preparation method further includes: before performing step 1), uniformly dispersing the nanomaterials in a dispersion solvent and ultrasonically treating them to form a nanomaterial dispersion, then separating the nanomaterials from the dispersion solvent and drying them, wherein the dispersion solvent includes ethanol, and the ultrasonic treatment time is 0.5 to 2 hours.
[0061] Furthermore, the nanomaterial dispersion also includes a dispersant to prevent the spontaneous aggregation of nanoparticles due to their high surface energy.
[0062] Further, in step 4), the temperature of the growth zone is controlled at 650℃~1250℃ using the HVPE method, the pressure in the reaction chamber is 250~650mbar, N2 is used as the carrier gas, the total carrier gas flow rate is 2000~6000ml, and the source inflow V / III value is controlled at 10~100, so as to grow a thick film layer of III-V compound on the III-V compound template layer.
[0063] Furthermore, in step 5), the substrate is peeled off by at least laser ablation, chemical etching, or polishing.
[0064] For more specific implementation examples, please refer to [link / reference]. Figure 1 The diagram illustrates the fabrication process for a high-quality III-V compound substrate (taking a GaN substrate as an example) by spin-coating a TMG source mixed precursor layer. This involves spin-coating a TMG source mixed precursor with uniformly dispersed nanoparticles (i.e., the aforementioned "nanomaterials") onto the substrate, followed by GaN substrate growth via MOCVD epitaxial growth and HVPE technology. The specific steps include:
[0065] 1) Preparation of nanoparticle dispersion
[0066] Nanoparticles are added to a dispersion solvent and mixed. Citric acid with a mass fraction of 0.2% is added as a dispersant to prevent the nanoparticles from spontaneously agglomerating due to their high surface energy. The nanoparticles are uniformly dispersed in the solvent under ultrasonic conditions of 50–150°C to form a nanoparticle dispersion.
[0067] In this process, anhydrous ethanol solvent is used, and nanoparticles with a diameter of 5–500 nm are added and sonicated for 0.5–2 hours.
[0068] 2) Preparation of nanoparticle TMG source hybrid precursor
[0069] The nanoparticles were separated from the solvent, dried rapidly, and immediately mixed with an appropriate amount of high-purity TMG source precursor. The mixture was then sonicated for 10 to 60 minutes under certain temperature (5 to 40°C) conditions to obtain a TMG source mixed precursor with uniformly dispersed nanoparticles.
[0070] 3) Spin-coated nanoparticle TMG source hybrid precursor
[0071] In a glove box N2 atmosphere, a TMG source mixed precursor with dispersed nanoparticles was spin-coated onto a substrate using a spin-coating method, forming a TMG source mixed precursor source coating layer with a thickness of 20nm to 2000nm with dispersed nanoparticles on the substrate.
[0072] 4) GaN template layer grown by MOCVD method
[0073] The substrate with the mixed precursor coating is placed in the reaction chamber of the MOCVD growth equipment, a TMG source is introduced and maintained for a certain time, the temperature is raised and NH3 and H2 are introduced for annealing and recrystallization, and a GaN template layer with a thickness of 0.01 to 1 μm is grown.
[0074] In this process, a sapphire substrate with a TMG source mixed precursor coating is placed in an MOCVD reaction chamber, the pressure is set to 100-600 mbar, the temperature is set to 500℃-1200℃, and NH3 and H2 are introduced for annealing and recrystallization for 10s-100s.
[0075] 5) Growth of GaN thick films using HVPE method
[0076] GaN thick films with a thickness of 100–1000 μm were grown on GaN template layers using the HVPE method.
[0077] The growth zone temperature was controlled at 650℃~1250℃ using the HVPE method, the pressure in the reaction chamber was 250~650mbar, N2 was used as the carrier gas, the total carrier gas flow rate was 2000~6000ml, and the source inflow V / III value was controlled at 10~100 to grow a GaN thick film layer on the GaN template layer.
[0078] 6) Substrate peeling
[0079] Among them, the substrate is peeled off by laser lift-off, chemical etching or grinding to obtain a high-quality GaN substrate.
[0080] Another aspect of the present invention provides a high-quality III-V compound substrate prepared by the aforementioned method.
[0081] The technical solutions, implementation processes, and principles of the embodiments of the present invention will be further explained below in conjunction with the accompanying drawings.
[0082] Example 1
[0083] 1) Preparation of Ni nanoparticle dispersion
[0084] Anhydrous ethanol was used, along with 30% by mass of nano-Ni powder with a diameter of 30-80 nm and 0.15% by mass of citric acid dispersant, and the mixture was sonicated at room temperature for 2 hours.
[0085] 2) Preparation of Ni nanoparticle TMG source
[0086] Ni nanoparticles were separated from the solvent, rapidly dried, and immediately mixed with a high-purity TMG source. The mass fraction of Ni nanoparticles was 40%. The mixture was sonicated at 40°C for 60 min to obtain a TMG source mixed precursor with uniformly dispersed Ni nanoparticles.
[0087] 3) Spin-coated Ni nanoparticle TMG source hybrid precursor
[0088] In a glove box N2 atmosphere, a spin coater was used to spin coat the Ni nanoparticle TMG source mixed precursor onto a sapphire substrate at a speed of 4000 rpm, forming a uniformly dispersed Ni nanoparticle TMG source mixed precursor coating layer with a thickness of 30 nm on the substrate.
[0089] 4) GaN template layer grown by MOCVD method
[0090] A sapphire substrate coated with a TMG source mixed precursor containing dispersed Ni nanoparticles was placed in an MOCVD reaction chamber. The pressure was set to 300 mbar, a TMG source was introduced, the temperature was set to 1200 °C, and NH3 and H2 were introduced for annealing and recrystallization for 10 s. The flow ratio of NH3 to H2 was 10:1, and a GaN template layer with a thickness of 0.01 μm was grown.
[0091] 5) Growth of GaN thick films using HVPE method
[0092] The growth zone temperature was controlled at 1050℃ and the reaction chamber pressure was 500mbar using the HVPE method. N2 was used as the carrier gas with a total carrier gas flow rate of 4000ml. The source inflow V / III value was controlled at 50. A GaN thick film with a thickness of 100μm was grown on the GaN template layer.
[0093] 6) Substrate peeling
[0094] A laser lift-off method was used to remove the sapphire substrate and obtain the GaN substrate.
[0095] Example 2
[0096] 1) Preparation of Ni nanoparticle dispersion
[0097] Anhydrous ethanol was used, along with 30% by mass of nano-Ni powder with a diameter of 30-80 nm and 0.15% by mass of citric acid dispersant, and the mixture was sonicated at room temperature for 2 hours.
[0098] 2) Preparation of Ni nanoparticle TMG source
[0099] Ni nanoparticles were separated from the solvent, rapidly dried, and immediately mixed with a high-purity TMG source. The mass fraction of Ni nanoparticles was 40%. The mixture was sonicated at 40°C for 60 min to obtain a TMG source mixed precursor with uniformly dispersed Ni nanoparticles.
[0100] 3) Spin-coated Ni nanoparticle TMG source hybrid precursor
[0101] In a glove box N2 atmosphere, a spin coater was used to spin coat the Ni nanoparticle TMG source mixed precursor onto a sapphire substrate at a speed of 4000 rpm, forming a uniformly dispersed Ni nanoparticle TMG source mixed precursor coating layer with a thickness of 800 nm on the substrate.
[0102] 4) GaN template layer grown by MOCVD method
[0103] A sapphire substrate coated with a TMG source mixed precursor containing dispersed Ni nanoparticles was placed in an MOCVD reaction chamber. The pressure was set to 300 mbar, a TMG source was introduced, the temperature was set to 1200 °C, and NH3 and H2 were introduced for annealing and recrystallization for 40 s. The flow ratio of NH3 to H2 was 20:1, and a GaN template layer with a thickness of 0.5 μm was grown.
[0104] 5) Growth of GaN thick films using HVPE method
[0105] The growth zone temperature was controlled at 1050℃ and the reaction chamber pressure was 400mbar using the HVPE method. N2 was used as the carrier gas with a total carrier gas flow rate of 4000ml. The source inflow V / III value was controlled at 50. A GaN thick film with a thickness of 500μm was grown on the GaN template layer.
[0106] 6) Substrate peeling
[0107] A laser lift-off method was used to remove the sapphire substrate and obtain the GaN substrate.
[0108] Example 3
[0109] 1) Preparation of Ni nanoparticle dispersion
[0110] Anhydrous ethanol was used, along with 30% by mass of nano-Ni powder with a diameter of 30-80 nm and 0.15% by mass of citric acid dispersant, and the mixture was sonicated at room temperature for 2 hours.
[0111] 2) Preparation of Ni nanoparticle TMG source
[0112] Ni nanoparticles were separated from the solvent, rapidly dried, and immediately mixed with a high-purity TMG source. The mass fraction of Ni nanoparticles was 40%. The mixture was sonicated at 40°C for 60 min to obtain a TMG source mixed precursor with uniformly dispersed Ni nanoparticles.
[0113] 3) Spin-coated Ni nanoparticle TMG source hybrid precursor
[0114] In a glove box N2 atmosphere, a spin coater was used to spin coat the Ni nanoparticle TMG source mixed precursor onto a sapphire substrate at a speed of 4000 rpm, forming a uniformly dispersed Ni nanoparticle TMG source mixed precursor coating layer with a thickness of 1800 nm on the substrate.
[0115] 4) GaN template layer grown by MOCVD method
[0116] A sapphire substrate with a TMG source mixed precursor coating containing dispersed Ni nanoparticles was placed in an MOCVD reaction chamber. The pressure was set to 300 mbar, a TMG source was introduced, the temperature was set to 1200 °C, and NH3 and H2 were introduced for annealing and recrystallization for 100 s. The flow ratio of NH3 to H2 was 50:1, and a GaN template layer with a thickness of 1 μm was grown.
[0117] 5) Growth of GaN thick films using HVPE method
[0118] The growth zone temperature was controlled at 1050℃ and the reaction chamber pressure at 550mbar using the HVPE method. N2 was used as the carrier gas with a total carrier gas flow rate of 4000ml. The source inflow V / III value was controlled at 50. A GaN thick film with a thickness of 1000μm was grown on the GaN template layer.
[0119] 6) Substrate peeling
[0120] A laser lift-off method was used to remove the sapphire substrate and obtain the GaN substrate.
[0121] The thickness of the GaN thick film can be matched by adjusting the thickness of the GaN template layer in Embodiments 1, 2 and 3 of the present invention, so as to obtain a GaN thick film with a complete surface, no cracks and low defect density.
[0122] In this case, the inventors also used spin-coating of different uniformly dispersed metal nanoparticles (such as Au, Ag, Fe, Co, Mn, Ti, Mg, Al, Ga, In, etc.) as TMG source precursor layers as buffer layers. Testing showed that this buffer layer, acting as a stress release agent, could reduce dislocation density and residual stress, thereby improving the crystal quality of subsequent GaN materials. The dislocation density of the GaN substrate film was controlled at 1×10⁻⁶. 6 cm -2 Within the order of magnitude.
[0123] Example 4
[0124] 1) Preparation of Si3N4 nanoparticle dispersion
[0125] Anhydrous ethanol was used, along with 10% by mass of Si3N4 nanoparticles with a diameter of 30–80 nm and 0.15% by mass of citric acid dispersant. The mixture was then sonicated at room temperature for 40 min.
[0126] 2) Preparation of Si3N4 nanoparticle TMG source
[0127] Si3N4 nanoparticles were separated from the solvent, rapidly dried, and immediately mixed with a high-purity TMG source. The mass fraction of Si3N4 nanoparticles was 10%. The mixture was sonicated at 25°C for 30 min to obtain a TMG source mixed precursor with uniformly dispersed Si3N4 nanoparticles.
[0128] 3) Spin-coated Si3N4 nanoparticle TMG source hybrid precursor
[0129] In a glove box N2 atmosphere, a spin coater was used to spin coat the Si3N4 nanoparticle TMG source mixed precursor onto a sapphire substrate at a speed of 4000 rpm, forming a uniformly dispersed Si3N4 nanoparticle TMG source mixed precursor coating layer with a thickness of 80 nm on the substrate.
[0130] 4) GaN template layer grown by MOCVD method
[0131] A sapphire substrate coated with a TMG source mixed precursor containing dispersed Si3N4 nanoparticles was placed in an MOCVD reaction chamber. The pressure was set to 300 mbar, a TMG source was introduced, the temperature was set to 1200 °C, and NH3 and H2 were introduced for annealing and recrystallization for 15 s. The flow ratio of NH3 to H2 was 80:1, and a GaN template layer with a thickness of 0.6 μm was grown.
[0132] 5) Growth of GaN thick films using HVPE method
[0133] The growth zone temperature was controlled at 1000℃ and the reaction chamber pressure at 500mbar using the HVPE method. N2 was used as the carrier gas with a total carrier gas flow rate of 4000ml. The source inflow V / III value was controlled at 50. A GaN thick film with a thickness of 650μm was grown on the GaN template layer.
[0134] 6) Substrate peeling
[0135] A laser lift-off method was used to remove the sapphire substrate and obtain the GaN substrate.
[0136] Example 5
[0137] 1) Preparation of Al2O3 nanoparticle dispersion
[0138] Anhydrous ethanol was used, and 15% by mass of Al2O3 nanoparticles with a diameter of 30-80 nm were added, along with 0.15% by mass of citric acid dispersant. The mixture was then sonicated at room temperature for 30 min.
[0139] 2) Preparation of Al2O3 nanoparticle TMG source
[0140] Al2O3 nanoparticles were separated from the solvent, rapidly dried, and immediately mixed with a high-purity TMG source. The mass fraction of Al2O3 nanoparticles was 15%. The mixture was sonicated at 15°C for 60 min to obtain a TMG source mixed precursor with uniformly dispersed Al2O3 nanoparticles.
[0141] 3) Spin-coated Al2O3 nanoparticle TMG source hybrid precursor
[0142] In a glove box N2 atmosphere, an Al2O3 nanoparticle TMG source mixed precursor was spin-coated onto a sapphire substrate at a speed of 4000 rpm using a spin coater, forming a uniformly dispersed Al2O3 nanoparticle TMG source mixed precursor coating layer with a thickness of 80 nm on the substrate.
[0143] 4) GaN template layer grown by MOCVD method
[0144] A sapphire substrate coated with a TMG source mixed precursor containing dispersed Al2O3 nanoparticles was placed in an MOCVD reaction chamber. The pressure was set to 200 mbar, a TMG source was introduced, the temperature was set to 1200 °C, and NH3 and H2 were introduced for annealing and recrystallization for 30 s. The flow ratio of NH3 to H2 was 100:1, and a GaN template layer with a thickness of 0.4 μm was grown.
[0145] 5) Growth of GaN thick films using HVPE method
[0146] The growth zone temperature was controlled at 1050℃ and the reaction chamber pressure was 600mbar using the HVPE method. N2 was used as the carrier gas with a total carrier gas flow rate of 4000ml. The source inflow WIII value was controlled at 50. A GaN thick film with a thickness of 350μm was grown on the GaN template layer.
[0147] 6) Substrate peeling
[0148] A laser lift-off method was used to remove the sapphire substrate and obtain the GaN substrate.
[0149] Testing revealed that, in this embodiment of the invention, spin-coating different uniformly dispersed nanoparticle TMG source precursor layers as a buffer layer can reduce dislocation density and residual stress, thereby improving the crystal quality of subsequent GaN materials. The dislocation density of the GaN substrate film was controlled at 10-1. 5 cm -2The order of magnitude is that the half-width at half-maximum (FWHM) of the rocking curves in the (002) and (102) planes of X-ray dual-crystal diffraction (XRD) tests is less than 100 arcsec.
[0150] In Examples 4 and 5 of this invention, a GaN thick film substrate was grown using Si3N4 and Al2O3 nanoparticles. Similarly, the thickness of the GaN template layer can be adjusted to match the thickness requirements of the GaN thick film substrate, resulting in a GaN thick film with a complete surface, no cracks, and low defect density.
[0151] Example 6
[0152] 1) Preparation of graphene dispersion
[0153] Anhydrous ethanol was used, along with 5% by mass of graphene nanoparticles with a diameter of 300–500 nm and 0.15% by mass of citric acid dispersant. The mixture was then sonicated at room temperature for 30 min.
[0154] 2) Preparation of TMG source from graphene nanoparticles
[0155] Graphene nanoparticles were separated from the solvent, quickly dried, and immediately mixed with a high-purity TMG source. The mass fraction of the graphene nanoparticles was 5%, and the mixture was sonicated at 25°C for 45 min to obtain a TMG source mixed precursor with uniformly dispersed graphene nanoparticles.
[0156] 3) Spin-coated graphene nanoparticle TMG source hybrid precursor
[0157] In a glove box N2 atmosphere, a spin coater was used to spin coat the graphene nanoparticle TMG source mixed precursor onto a sapphire substrate at a speed of 4000 rpm, forming a 2000 nm thick uniformly dispersed graphene nanoparticle TMG source mixed precursor coating layer on the substrate.
[0158] 4) GaN template layer grown by MOCVD method
[0159] A sapphire substrate with a TMG source and precursor coating containing dispersed graphene nanoparticles was placed in an MOCVD reaction chamber. The pressure was set to 100 mbar, a TMG source was introduced, the temperature was set to 1200 °C, and NH3 and H2 were introduced for annealing and recrystallization for 100 s. The flow ratio of NH3 to H2 was 50:1, and a GaN template layer with a thickness of 0.5 μm was grown.
[0160] 5) Growth of GaN thick films using HVPE method
[0161] The growth zone temperature was controlled at 1000℃ and the reaction chamber pressure at 650mbar using the HVPE method. N2 was used as the carrier gas with a total carrier gas flow rate of 2000ml. The source inflow V / III value was controlled at 100. A GaN thick film with a thickness of 950μm was grown on the GaN template layer.
[0162] 6) Substrate peeling
[0163] A laser lift-off method was used to remove the sapphire substrate and obtain the GaN substrate.
[0164] Example 7
[0165] 1) Preparation of TiO2 nanoparticle dispersion
[0166] Anhydrous ethanol was used, and 30% by mass of TiO2 nanoparticles with a diameter of 30-80 nm were added, along with 0.15% by mass of citric acid dispersant. The mixture was then sonicated at room temperature for 2 hours.
[0167] 2) Preparation of TiO2 nanoparticle TMG source
[0168] TiO2 nanoparticles were separated from the solvent, rapidly dried, and immediately mixed with a high-purity TMG source. The mass fraction of TiO2 nanoparticles was 28%. The mixture was sonicated at 5°C for 50 min to obtain a TMG source mixed precursor with uniformly dispersed TiO2 nanoparticles.
[0169] 3) Spin-coated TiO2 nanoparticle TMG source hybrid precursor
[0170] In a glove box N2 atmosphere, a spin coater was used to spin coat TiO2 nanoparticle TMG source mixed precursor onto a sapphire substrate at a speed of 4000 rpm, forming a uniformly dispersed TiO2 nanoparticle TMG source mixed precursor coating layer with a thickness of 2000 nm on the substrate.
[0171] 4) GaN template layer grown by MOCVD method
[0172] A sapphire substrate with a TMG source mixed precursor coating containing dispersed TiO2 nanoparticles was placed in an MOCVD reaction chamber. The pressure was set to 600 mbar, a TMG source was introduced, the temperature was set to 1200 °C, and NH3 and H2 were introduced for annealing and recrystallization for 100 s. The flow ratio of NH3 to H2 was 30:1, and a GaN template layer with a thickness of 0.5 μm was grown.
[0173] 5) Growth of GaN thick films using HVPE method
[0174] The growth zone temperature was controlled at 1250℃ and the reaction chamber pressure at 250mbar using the HVPE method. N2 was used as the carrier gas with a total carrier gas flow rate of 6000ml. The source inflow V / III value was controlled at 50. A GaN thick film with a thickness of 850μm was grown on the GaN template layer.
[0175] 6) Substrate peeling
[0176] A laser lift-off method was used to remove the sapphire substrate and obtain the GaN substrate.
[0177] In this case, the inventors also used spin-coating of different uniformly dispersed metal oxide nanoparticles (such as ZnO, Fe3O4, Ta2O5, SnO2, ZrO2, etc.) as TMG source precursor layers as buffer layers. Testing showed that this layer, acting as a stress release agent, could reduce dislocation density and residual stress, thereby improving the crystal quality of subsequent GaN materials. The dislocation density of the GaN substrate film was controlled at 1×10⁻⁶. 6 cm -2 Within the order of magnitude.
[0178] Example 8
[0179] 1) Preparation of GaN nanoparticle dispersion
[0180] Anhydrous ethanol was used, along with 30% by mass of GaN nanoparticles with a diameter of 30–80 nm and 0.15% by mass of citric acid dispersant, and the mixture was sonicated at room temperature for 2 hours.
[0181] 2) Preparation of GaN nanoparticle TMG source
[0182] GaN nanoparticles were separated from the solvent, rapidly dried, and immediately mixed with a high-purity TMG source. The mass fraction of GaN nanoparticles was 24%. The mixture was sonicated at 5°C for 50 min to obtain a TMG source mixed precursor with uniformly dispersed GaN nanoparticles.
[0183] 3) Spin-coated GaN nanoparticle TMG source hybrid precursor
[0184] In a glove box N2 atmosphere, a spin coater was used to spin coat the GaN nanoparticle TMG source mixed precursor onto a sapphire substrate at a speed of 4000 rpm, forming a uniformly dispersed GaN nanoparticle TMG source mixed precursor coating layer with a thickness of 2000 nm on the substrate.
[0185] 4) GaN template layer grown by MOCVD method
[0186] A sapphire substrate with a TMG source mixed precursor coating containing dispersed GaN nanoparticles was placed in an MOCVD reaction chamber. The pressure was set to 300 mbar, a TMG source was introduced, the temperature was set to 1200 °C, and NH3 and H2 were introduced for annealing and recrystallization for 100 s. The flow ratio of NH3 to H2 was 60:1, and a GaN template layer with a thickness of 1 μm was grown.
[0187] 5) Growth of GaN thick films using HVPE method
[0188] The growth zone temperature was controlled at 1200℃ and the reaction chamber pressure at 300mbar using the HVPE method. N2 was used as the carrier gas with a total carrier gas flow rate of 6000ml. The source inflow V / III value was controlled at 100. A GaN thick film with a thickness of 880μm was grown on the GaN template layer.
[0189] 6) Substrate peeling
[0190] A laser lift-off method was used to remove the sapphire substrate and obtain the GaN substrate.
[0191] In this case, the inventors also used spin-coating of different uniformly dispersed inorganic nanoparticles (such as SiO2, TiN, BN, AlN, InN, ScAlN, etc.) as TMG source precursor layers as buffer layers. Testing showed that this buffer layer, acting as a stress release agent, could reduce dislocation density and residual stress, thereby improving the crystal quality of subsequent GaN materials. The dislocation density of the GaN substrate film was controlled at 1×10⁻⁶. 6 cm -2 Within the order of magnitude.
[0192] Example 9
[0193] 1) Preparation of Si dispersion
[0194] Anhydrous ethanol was used, along with 5% by mass Si nanoparticles with a diameter of 5000–800 nm and 0.15% by mass citric acid dispersant. The mixture was then sonicated at room temperature for 30 min.
[0195] 2) Preparation of Si nanoparticle TMG source
[0196] Si nanoparticles were separated from the solvent, rapidly dried, and immediately mixed with a high-purity TMG source. The mass fraction of the Si nanoparticles was 5%. The mixture was sonicated at 25°C for 10 min to obtain a TMG source mixed precursor with uniformly dispersed Si nanoparticles.
[0197] 3) Spin-coated Si nanoparticle TMG source hybrid precursor
[0198] In a glove box N2 atmosphere, a spin coater was used to spin coat the Si nanoparticle TMG source mixed precursor onto a sapphire substrate at a speed of 4000 rpm, forming a uniformly dispersed Si nanoparticle TMG source mixed precursor coating layer with a thickness of 2000 nm on the substrate.
[0199] 4) GaN template layer grown by MOCVD method
[0200] A sapphire substrate coated with a TMG source mixed precursor containing dispersed Si nanoparticles was placed in an MOCVD reaction chamber. The pressure was set to 500 mbar, a TMG source was introduced, the temperature was set to 1125 °C, and NH3 and H2 were introduced for annealing and recrystallization for 10 s. The flow ratio of NH3 to H2 was 100:1, and a GaN template layer with a thickness of 0.5 μm was grown.
[0201] 5) Growth of GaN thick films using HVPE method
[0202] The growth zone temperature was controlled at 1100℃ and the reaction chamber pressure at 650mbar using the HVPE method. N2 was used as the carrier gas with a total carrier gas flow rate of 2000ml. The source inflow V / III value was controlled at 50. A GaN thick film with a thickness of 350μm was grown on the GaN template layer.
[0203] 6) Substrate peeling
[0204] A laser lift-off method was used to remove the sapphire substrate and obtain the GaN substrate.
[0205] In this case, the inventors also used spin-coating different uniformly dispersed non-metallic nanoparticles (such as C, SiC, B4C, BN, etc.) as TMG source precursor layers as buffer layers. Testing showed that this buffer layer, acting as a stress release agent, could reduce dislocation density and residual stress, thereby improving the crystal quality of subsequent GaN materials. The dislocation density of the GaN substrate film was controlled at 1×10⁻⁶. 6 cm -2 Within the order of magnitude.
[0206] Correspondingly, the inventors in this case also used spin-coated uniformly dispersed organic compound nanoparticles, such as a TMG source precursor layer of polystyrene, as a buffer layer, and the test results were basically consistent with those of the aforementioned embodiments.
[0207] Example 10
[0208] 1) Preparation of Ni nanoparticle dispersion
[0209] Anhydrous ethanol was used, along with 30% by mass of nano-Ni powder with a diameter of 30-80 nm and 0.15% by mass of citric acid dispersant, and the mixture was sonicated at room temperature for 2 hours.
[0210] 2) Preparation of Ni nanoparticles with dimethylethyl indium
[0211] Ni nanoparticles were separated from the solvent, quickly dried, and immediately mixed with a high-purity dimethyl ethyl indium source. The mass fraction of Ni nanoparticles was 40%. The mixture was ultrasonicated at 40°C for 30 min to obtain a uniformly dispersed dimethyl ethyl indium source mixed precursor of Ni nanoparticles.
[0212] 3) Spin-coated Ni nanoparticle trimethylindium source hybrid precursor
[0213] In a glove box N2 atmosphere, a spin coater was used to spin coat a Ni nanoparticle dimethyl ethyl indium source mixed precursor onto a silicon substrate at a speed of 4000 rpm, forming a uniformly dispersed Ni nanoparticle dimethyl ethyl indium source mixed precursor coating layer with a thickness of 25 nm on the substrate.
[0214] 4) MOCVD method for growing InAs template layers
[0215] A silicon substrate coated with a dimethyl ethyl indium source mixed precursor containing dispersed Ni nanoparticles was placed in an MOCVD reaction chamber. The pressure was set to 400 mbar, dimethyl ethyl indium was introduced, the temperature was set to 500 °C, tert-butyl arsenide (TBA) and H2 were introduced for annealing and recrystallization for 10 s, and the flow ratio of TBA to H2 was 15:1. An InAs template layer with a thickness of 0.01 μm was grown.
[0216] 5) Growth of InAs thick films using HVPE method
[0217] The growth zone temperature was controlled at 650℃ and the reaction chamber pressure at 500mbar using the HVPE method. N2 was used as the carrier gas with a total carrier gas flow rate of 4000ml. The source inflow V / III value was controlled at 10. A 100μm thick InAs film layer was grown on the InAs template layer.
[0218] 6) Substrate peeling
[0219] The silicon substrate was removed by laser lift-off to obtain the InAs substrate.
[0220] Example 11
[0221] 1) Preparation of Ni nanoparticle dispersion
[0222] Anhydrous ethanol was used, along with 30% by mass of nano-Ni powder with a diameter of 30-80 nm and 0.15% by mass of citric acid dispersant, and the mixture was sonicated at room temperature for 2 hours.
[0223] 2) Preparation of Ni nanoparticles with dimethylethyl indium
[0224] Ni nanoparticles were separated from the solvent, quickly dried, and immediately mixed with high-purity dimethyl ethyl indium. The mass fraction of Ni nanoparticles was 40%. The mixture was sonicated at 20°C for 30 min to obtain a dimethyl ethyl indium source mixed precursor with uniformly dispersed Ni nanoparticles.
[0225] 3) Spin-coated Ni nanoparticle dimethylethyl indium mixed precursor
[0226] In a glove box N2 atmosphere, a spin coater was used to spin coat a Ni nanoparticle dimethyl ethyl indium source mixed precursor onto a silicon substrate at a speed of 4000 rpm, forming a uniformly dispersed Ni nanoparticle dimethyl ethyl indium source mixed precursor coating layer with a thickness of 100 nm on the substrate.
[0227] 4) MOCVD method for growing InP template layers
[0228] A silicon substrate coated with a dimethyl ethyl indium source mixed precursor containing dispersed Ni nanoparticles was placed in an MOCVD reaction chamber. The pressure was set to 500 mbar, a dimethyl ethyl indium source was introduced, the temperature was set to 650 °C, and tert-butyl phosphorus (TBP) and H2 were introduced for annealing and recrystallization for 100 s. The TBP to H2 flow rate ratio was 20:1, and an InP template layer with a thickness of 0.5 μm was grown.
[0229] 5) Growth of InP thick films using HVPE method
[0230] The growth zone temperature was controlled at 720℃ and the reaction chamber pressure at 300mbar using the HVPE method. N2 was used as the carrier gas with a total carrier gas flow rate of 5000ml. The source inflow V / III value was controlled at 15. A 350μm thick InP film layer was grown on the InP template layer.
[0231] 6) Substrate peeling
[0232] The silicon substrate was removed by laser lift-off to obtain the InP substrate.
[0233] Example 12
[0234] 1) Preparation of Ni nanoparticle dispersion
[0235] Anhydrous ethanol was used, along with 30% by mass of nano-Ni powder with a diameter of 30-80 nm and 0.15% by mass of citric acid dispersant, and the mixture was sonicated at room temperature for 2 hours.
[0236] 2) Preparation of Ni nanoparticle TMG source
[0237] Ni nanoparticles were separated from the solvent, rapidly dried, and immediately mixed with a high-purity TMG source. The mass fraction of Ni nanoparticles was 10%. The mixture was ultrasonicated at 40°C for 60 min to obtain a TMG source mixed precursor with uniformly dispersed Ni nanoparticles.
[0238] 3) Spin-coated Ni nanoparticle TMG source hybrid precursor
[0239] In a glove box N2 atmosphere, a spin coater was used to spin coat the Ni nanoparticle TMG source mixed precursor onto a silicon carbide substrate at a speed of 4000 rpm, forming a uniformly dispersed Ni nanoparticle TMG source mixed precursor coating layer with a thickness of 60 nm on the substrate.
[0240] 4) Growth of GaAs template layer by MOCVD method
[0241] A silicon carbide substrate coated with a TMG source mixed precursor containing dispersed Ni nanoparticles was placed in an MOCVD reaction chamber. The pressure was set to 300 mbar, a TMG source was introduced, the temperature was set to 680 °C, and AsH3 and H2 were introduced for annealing and recrystallization for 10 s. The flow ratio of AsH3 to H2 was 30:1, and a GaAs template layer with a thickness of 0.01 μm was grown.
[0242] 5) Growth of GaAs thick films using HVPE method
[0243] The growth zone temperature was controlled at 650℃ and the reaction chamber pressure at 300mbar using the HVPE method. N2 was used as the carrier gas with a total carrier gas flow rate of 4000ml. The source inflow V / III value was controlled at 20. A GaAs thick film with a thickness of 100μm was grown on the GaAs template layer.
[0244] 6) Substrate peeling
[0245] A laser lift-off method was used to remove the silicon carbide substrate and obtain the GaAs substrate.
[0246] Examples 10, 11, and 12 describe the fabrication of InAs, InP, and GaAs substrates with smooth surfaces and low defect densities. The dislocation density of the InAs substrate is typically 5 × 10⁻⁶. 3 cm -2 Carrier concentration 4.2 × 10 15 cm -3 The dislocation density of the InP substrate is 3.5 × 10⁻⁶. 3 cm -2 The electron concentration is 3.1 × 10⁻⁶. 15c m -3 The dislocation density of the GaAs substrate is 2 × 10⁻⁶. 3 cm -2 The carrier concentration is 2.2 × 10⁻⁶.15 cm -3 Furthermore, compared to liquid-sealed Czochralski polished surfaces, it has a lower content of impurities such as O, making it suitable for epitaxial processes of high-end devices.
[0247] Example 13
[0248] 1) Preparation of Ni nanoparticle dispersion
[0249] Anhydrous ethanol was used, along with 30% by mass of nano-Ni powder with a diameter of 30-80 nm and 0.15% by mass of citric acid dispersant, and the mixture was sonicated at room temperature for 2 hours.
[0250] 2) Preparation of Ni nanoparticle trimethylaluminum source
[0251] Ni nanoparticles were separated from the solvent, quickly dried, and immediately mixed with a high-purity trimethylaluminum source. The mass fraction of Ni nanoparticles was 45%. The mixture was sonicated at 40°C for 40 min to obtain a trimethylaluminum source mixed precursor with uniformly dispersed Ni nanoparticles.
[0252] 3) Spin-coated Ni nanoparticle trimethylaluminum source mixed precursor
[0253] In a glove box N2 atmosphere, a spin coater was used to spin coat a Ni nanoparticle trimethylaluminum source mixed precursor onto a sapphire substrate at a speed of 4000 rpm, forming a uniformly dispersed Ni nanoparticle trimethylaluminum source mixed precursor coating layer with a thickness of 60 nm on the substrate.
[0254] 4) Growth of AlN template layer by MOCVD method
[0255] A sapphire substrate coated with a trimethylaluminum source mixed precursor containing dispersed Ni nanoparticles was placed in an MOCVD reaction chamber. The pressure was set to 100 mbar, a trimethylaluminum source was introduced, the temperature was set to 1200 °C, and NH3 and H2 were introduced for annealing and recrystallization for 10 s. The flow rate ratio of NH3 to H2 was 50:1, and an AlN template layer with a thickness of 0.01 μm was grown.
[0256] 5) Growth of AlN thick films using HVPE method
[0257] The growth zone temperature was controlled at 1250℃ and the reaction chamber pressure at 250mbar using the HVPE method. N2 was used as the carrier gas with a total carrier gas flow rate of 4000ml. The source inflow V / II value was controlled at 20. An AlN thick film with a thickness of 100μm was grown on the AlN template layer.
[0258] 6) Substrate peeling
[0259] The sapphire substrate was removed by laser lift-off to obtain the AlN substrate.
[0260] Compare with Example 1
[0261] The difference between this comparative example and Example 1 is that no Ni nanoparticles were added to the TMG source.
[0262] The dislocation density of the final GaN substrate reached 5 × 10⁻⁶. 6 cm -2 This is an order of magnitude higher than that of Example 1.
[0263] Compare with Example 2
[0264] The difference between this comparative example and Example 3 is that: instead of using TMG source spin coating, the GaN template layer is directly grown by MOCVD epitaxy. As a result, the surface of the GaN thick film substrate exhibits unevenly distributed cracks and pits, making it difficult to obtain a high-quality GaN thick film substrate.
[0265] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
[0266] The above are merely specific embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of protection described in the claims.
Claims
1. A method for preparing a high-quality III-V compound substrate, characterized in that, include: Nanomaterials are uniformly mixed with a group III metal-organic source and ultrasonically treated at 5–40 °C for 10–60 min to obtain a group III metal-organic source mixed precursor containing uniformly dispersed nanomaterials. The group III metal-organic source mixed precursor is coated onto a substrate to obtain a group III metal-organic source mixed precursor coating layer. Then, the substrate with the group III metal-organic source mixed precursor coating layer is placed in an MOCVD reaction chamber, and a group III metal-organic source is introduced to raise the temperature of the reaction chamber to 500-1200°C. Annealing and recrystallization are carried out in a mixed atmosphere of group V element source and reducing gas to form uniformly distributed nanomaterials and group III-V compound nanostructures. Group III-V compounds are further grown to obtain a group III-V compound template layer. A thick film of III-V compound is grown on the template layer of the III-V compound to obtain a high-quality III-V compound substrate.
2. The preparation method according to claim 1, characterized in that: The nanomaterials include any one or more combinations of zero-dimensional nanomaterials, one-dimensional nanomaterials, two-dimensional nanomaterials, and three-dimensional nanomaterials.
3. The preparation method according to claim 1, characterized in that: The mass ratio of nanomaterials to group III metal-organic sources in the hybrid precursor is less than 1:
1.
4. The preparation method according to claim 1, characterized in that: The morphology of the nanomaterials includes any one or a combination of two or more of the following: nanoparticles, nanowires, nanofilms, and nanobulks.
5. The preparation method according to claim 1, characterized in that: The nanomaterials include any one or a combination of two or more of the following: metallic nanomaterials, non-metallic inorganic nanomaterials, and organic compound nanomaterials.
6. The preparation method according to claim 5, characterized in that: The nanomaterials include Si3N4, SiO2, GaN, AlN, InN, SiC, ScAlN, Al2O3, Si, C, TiC, TiN, WC, and WC-C. O Any one or more of the following: B4C, BN, TiB2, LaF3, MoS2, ZrB2, ZnS, ZnSe, ZnO, Fe3O4, Ta2O5, SnO2, TiO2, ZrO2, Ni, Au, Ag, Fe, Co, Mn, Ti, Mg, Al, Ga, In, polystyrene, perovskite, and graphene.
7. The preparation method according to claim 5, characterized in that: The diameter of the nanomaterial is 5–500 nm.
8. The preparation method according to claim 5, characterized in that: The nanomaterials include any one or a combination of two or more of the following: SiN, SiO2, GaN, AlN, InN, SiC, ScAlN, Al2O3, Si, C, TiC, TiN, BN, ZnS, ZnSe, ZnO, TiO2, Ni, Au, Ag, Fe, Co, Mn, Ti, Mg, Al, and graphene.
9. The preparation method according to claim 5, characterized in that: The nanomaterials include any one or a combination of two or more of Si3N4, SiO2, GaN, AlN, SiC, ScAlN, Al2O3, TiO2, Ni, Al, Ga, and graphene.
10. The preparation method according to claim 1, characterized in that: The group III metal-organic source contains any one or more of the group III elements indium, gallium, and aluminum; the group III metal-organic source includes a group III organic compound source, which includes any one or more of the indium source, gallium source, and aluminum source; the indium source includes any one or more of the trimethylindium, triethylindium, and dimethylethylindium; the gallium source includes any one or more of the trimethylgallium, triethylgallium, and triisopropylgallium; and the aluminum source includes any one or more of the trimethylaluminum, triethylaluminum, dimethylalanealuminum, dimethylaluminum hydride, and aluminum alkyl complexes.
11. The preparation method according to claim 1, characterized in that: The Group V element source includes any one or more combinations of nitrogen, phosphorus, and arsenic; the Group V element source includes any one or more combinations of nitrogen source, phosphorus source, and arsenic source; the nitrogen source includes any one or more combinations of NH3, organic amine compounds, and trap compounds; the organic amine compound includes alkylamine, the alkylamine includes tert-butylamine and / or n-propylamine, and the trap compound includes dimethyl trap; the phosphorus source includes PH3 and / or an organic phosphorus source, the organic phosphorus source includes tert-butylphosphine; the arsenic source includes AsH3 and / or an organic arsenic source, the organic arsenic source includes tert-butylarsenic.
12. The preparation method according to claim 1, characterized in that: The reducing gas includes H2.
13. The preparation method according to claim 1, characterized in that: The flow rate ratio of the group V element source to the reducing gas in the mixed atmosphere is 10:1 to 100:
1.
14. The preparation method according to claim 1, characterized in that, Includes the following steps: In an N2 atmosphere, the group III metal-organic source mixed precursor is coated onto a substrate using a spin coating method to form a group III metal-organic source mixed precursor coating layer with a thickness of 20 nm to 2000 nm on the substrate. A substrate coated with a mixed precursor of group III metal-organic source is placed in the reaction chamber of an MOCVD growth apparatus. The pressure in the reaction chamber is 100–600 mbar. A group III metal-organic source, which is a group III organic compound source, is introduced. The reaction chamber is heated to 500–1200 °C. A group V element source and a reducing gas are introduced for annealing and recrystallization for 10–100 s. Then, a group III-V compound template layer with a thickness of 0.01–1 μm is grown. A thick film of III-V compound with a thickness of 100-1000 μm was grown on the template layer of the III-V compound using the HVPE method. The substrate was peeled off to obtain a high-quality III-V compound substrate.
15. The preparation method according to claim 14, characterized in that... Also includes: Nanomaterials are uniformly dispersed in a dispersion solvent and ultrasonically treated to form a nanomaterial dispersion. The nanomaterials are then separated from the dispersion solvent and dried. The dispersion solvent includes ethanol, and the ultrasonic treatment time is 0.5 to 2 hours. The nanomaterial dispersion also includes a dispersant.
16. The preparation method according to claim 14, characterized in that: The substrate is made of materials including sapphire, silicon, or silicon carbide.
17. The preparation method according to claim 14, characterized in that: The temperature of the growth zone was controlled at 650℃~1250℃ and the pressure in the reaction chamber was controlled at 250~650mbar using the HVPE method. N2 was used as the carrier gas and the total carrier gas flow rate was 2000~6000ml. The source inflow V / III value was controlled at 10~100 to grow a thick film of III-V compound on the template layer of III-V compound.
18. The preparation method according to claim 14, characterized in that: The substrate is removed by at least laser stripping, chemical etching, or grinding.
19. A high-quality III-V compound substrate prepared by the method of any one of claims 1-18.
Citation Information
Patent Citations
Method for growing high-quality gallium nitride (GaN) crystals by using graphene or graphene oxide
CN103741220A
Method for growing high-quality gallium nitride (GaN) crystals by using hexagonal boron nitride nanosheets
CN103741221A
Preparation method of large-size GaN thick film
CN111463325A